2020
DOI: 10.1111/head.13919
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral, Interictal Serum S100B Levels are Not Increased in Chronic Migraine Patients

Abstract: Background The trigemino‐vascular system (TVS) plays a key role in migraine pathophysiology. Glial cells are abundant in the TVS system and mainly in the trigeminal ganglion. S100B protein is a calcium‐binding protein, found in the cytoplasm of glial cells in the central nervous system, which is released in response to inflammatory stimuli. Previous works analyzing S100B in migraineurs have offered contradictory results. Objective In this case‐control study, we analyzed serum levels of S100B as a possible biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Previous works analysing S100B in migraineurs have offered contradictory results. The first study in CM has shown S100B levels in the range of healthy controls (109).…”
Section: Neurochemistry: Biochemical Chronic Migraine Biomarkersmentioning
confidence: 99%
“…Previous works analysing S100B in migraineurs have offered contradictory results. The first study in CM has shown S100B levels in the range of healthy controls (109).…”
Section: Neurochemistry: Biochemical Chronic Migraine Biomarkersmentioning
confidence: 99%
“…This may imply that S100B is involved in the pathological process of the occurrence and development of migraine. In these two studies including data of patients with episodic migraine and chronic migraine, the S100B levels of both chronic and episodic migraine in the Riesco et al study were not significant increases from those in the control group (24), unlike the findings of Gönen et al (22). This may be related to the fact that preventive medication was not withdrawn before blood samples were collected in the Riesco et al study.…”
Section: Discussionmentioning
confidence: 77%
“…This may indicate that brain cell damage caused by local inflammation leads to the elevation of S100B levels. Subsequently, several studies found that the S100B level in migraine during the interictal period also increased (22,24,(26)(27)(28)(29)(30). These findings suggest that migraine may be an ongoing or progressive disorder with a subclinical course, rather than a paroxysmal disorder characterized by intermittent headaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A pilot RCT in CM patients revealed that ibudilast (a potential glia inhibitor) treatment did not reduce the frequency of headache, but it was well-tolerated [79]. In a case-control trial, serum levels of S100B were analyzed in EM and CM patients, and the results showed no interictal S100B elevation [80]. In EM and CM patients, the serum level of S100B was significantly higher compared to controls, and there was no difference between the two patient groups [81].…”
Section: Migrainementioning
confidence: 99%